Autoimmune thyroid diseases and pregnancy - Moleti, Mariacarla; Sturniolo, Giacomo; Mauro, Maria Di; Russo, Marco; Vermiglio, Francesco (Annals of Thyroid; Vol 3 (July 2018): Annals of Thyroid, 2018)
Thyroid autoimmunity affects 5–20% of the female population of childbearing age. Even in the absence of overt maternal thyroid dysfunction, thyroid autoimmunity has been reported to be associated with an increased risk of adverse pregnancy outcomes and impaired fetal neurodevelopment. Present evidence indicates that thyroid autoimmunity poses a risk for miscarriage and preterm delivery. By contrast, with regard to infertility most studies failed to find significantly different likelihood of pregnancy in euthyroid women with and without thyroid antibodies undergoing assisted reproduction procedures. Finally, uncertainty surrounds the role of thyroid autoantibodies on fetal and neonatal outcomes, since an increased risk for perinatal death, intrauterine growth restriction (IUGR), and respiratory distress syndrome has been inconsistently reported, and only few studies addressed the impact of maternal thyroperoxidase antibodies (TPOAbs) during pregnancy on cognitive functioning of the child, once again providing mixed results. Whether thyroid antibodies have a direct effect on neonatal outcomes, including neurodevelopment in the progeny, or whether the observed associations are related to maternal autoimmune-related thyroid insufficiency needs to be still clarified.